Numbness and bleeding from the ear following inferior alveolar nerve block: report of a case - Das, Joy R.; Vinod Vichattu, Sankar; George, Arun; James, Jinu Elizabeth; Paul, Sarah (International Journal of Research in Medical Sciences, 2023)
The inferior alveolar nerve block is a Mandibular nerve block given to anesthetize the mandibular teeth. Due to its proximity to other nerves and muscles and salivary glands it has many complications if the technique in which it is given is wrong. IANB usually presents with mild or minimal complications following it’s administration. The complications that arise are usually reversible when the action of the local anaesthetic wears off. These complications are usually associated with improper technique and anatomical variations, which can be rectified there itself with slight modifications. This is a very rare complication which has been reported where the patient has experienced numbness of the auricle on the side of inferior alveolar injection which lasted for an hour. This is seen due to the accidental anesthetic injection to the auriculotemporal nerve resulting in numbness. To perform successful inferior alveolar nerve blocks it is mandatory to be familiar with anatomical landmarks. Proper technique can reduce the complications.